Odpowiedzi

2009-10-05T21:26:26+02:00
Y=ax²+bx+c

(4,5)
5=a(4)²+b*4+c
5=16a+4b+c

(2,3)
3=a(2)²+2b+c
3=4a+2b+c

xw=-b/2a
2=-b/2a

mamy uklad
5=16a+4b+c
3=4a+2b+c
2=-b/2a

5=16a+4b+c
3=4a+2b+c
2=-b/2a obie strony razy -2a

5=16a+4(-4a)+c
3=4a+2(-4a)+c
-4a=b


5=c
3=4a-8a+5
-4a=b

c=5
4a=2
b=-4a

c=5
a=1/2
b=-4(1/2)=-2

y=1/2x²-2x+5


w odp jest bład bo f(4)=-5 w tym co podali a nie 5


b)(5,6)
6=25a +5b+c

(3,-2)
-2=9a+3b+c

xw=-b/2a
3=-b/2a
b=-6a
mamy uklad
6=25a +5b+c
-2=9a+3b+c
b=-6a

6=25a -30a+c
-2=9a-18a+c
b=-6a

6=-5a+c
-2=9a+c
b=-6a

6+5a=c
-2=-9a+6+5a
b=-6a

6+5a=c
4a=8
b=-6a

6+10=c
a=2
b=-12

c=16
a=2
b=-12

y=2x²-12x+16